Dexmedetomidine Pharmacokinetics in Neonates with Hypoxic-Ischemic Encephalopathy Receiving Hypothermia. (25th February 2020) - McAdams, Ryan M.; Pak, Daniel; Lalovic, Bojan; Phillips, Brian; Shen, Danny D.
Abstract : Dexmedetomidine is a promising sedative and analgesic for newborns with hypoxic-ischemic encephalopathy (HIE) undergoing therapeutic hypothermia (TH). Pharmacokinetics and safety of dexmedetomidine were evaluated in a phase I, single-center, open-label study to inform future trial strategies. We recruited 7 neonates ≥36 weeks' gestational age diagnosed with moderate-to-severe HIE, who received a continuous dexmedetomidine infusion during TH and the 6 h rewarming period. Time course of plasma dexmedetomidine concentration was characterized by serial blood sampling during and after the 64.8 ± 6.9 hours of infusion. Noncompartmental analysis yielded descriptive pharmacokinetic estimates: plasma clearance of 0.760 ± 0.155 L/h/kg, steady-state distribution volume of 5.22 ± 2.62 L/kg, and mean residence time of 6.84 ± 3.20 h. Naive pooled and population analyses according to a one-compartment model provided similar estimates of clearance and distribution volume. Overall, clearance was either comparable or lower, distribution volume was larger, and mean residence time or elimination half-life was longer in cooled newborns with HIE compared to corresponding estimates previously reported for uncooled (normothermic) newborns without HIE at comparable gestational and postmenstrual ages. As a result, plasma concentrations in cooled newborns with HIE rose more slowly in the initial hours of infusion compared to predicted concentration-time profiles based on reported pharmacokinetic parameters in normothermic newborns without HIE, while similar steady-state levels were achieved. No acute adverse events were associated with dexmedetomidine treatment. While dexmedetomidine appeared safe for neonates with HIE during TH at infusion doses up to 0.4  μ g/kg/h, a loading dose strategy may be needed to overcome the initial lag in rise of plasma dexmedetomidine concentration.